2003
DOI: 10.1002/ejic.200300107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight Gained into the Ligand Substitution Reactions of Bis(o‐benzosemiquinonediiminato)(triphenylphosphane)cobalt(III) − Kinetic, Solvent, and Volume Profile Studies

Abstract: The ligand substitution reactions of bis (o-benzosemiquinonediiminato)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…32 Distortion arising from the interaction of the axial alkyl group with the equatorial ligand can be ascribed to (a) changes in the C-Co-N(eq) bond angles; (b) widening of the Co-CH 2 -R′ angles and shortening of the Co-R bond lengths; (c) lengthening of the Co-C bond; (d) deformation of the equatorial ligand unit. 32 It can be concluded that the variety of chelates, R groups, entering ligands, and solvents selected in this and our earlier studies [1][2][3][4][5][6] enables a systematic tuning of the lability of alkyl cobalt(III) complexes, which results in a systematic tuning of the ligand displacement process in terms of a dissociative interchange (I d ) and a limiting dissociative (D) mechanism.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…32 Distortion arising from the interaction of the axial alkyl group with the equatorial ligand can be ascribed to (a) changes in the C-Co-N(eq) bond angles; (b) widening of the Co-CH 2 -R′ angles and shortening of the Co-R bond lengths; (c) lengthening of the Co-C bond; (d) deformation of the equatorial ligand unit. 32 It can be concluded that the variety of chelates, R groups, entering ligands, and solvents selected in this and our earlier studies [1][2][3][4][5][6] enables a systematic tuning of the lability of alkyl cobalt(III) complexes, which results in a systematic tuning of the ligand displacement process in terms of a dissociative interchange (I d ) and a limiting dissociative (D) mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…The Co-C bond lengthens from 1.990 to 2.044 Å as the bulk of the alkyl group increases from CH 3 to CH 2 CMe 3 in the case of the dimethylglyoximate complex, and clearly depends on the steric interaction between the axial alkyl and the equatorial ligands. 31 In addition, the hybridization of the carbon atom affects the Co-C bond length, which was found to be 2.00, 1.96, and 1.90 Å for sp 3 , sp 2 , and sp hybridization, respectively. 32 Distortion arising from the interaction of the axial alkyl group with the equatorial ligand can be ascribed to (a) changes in the C-Co-N(eq) bond angles; (b) widening of the Co-CH 2 -R′ angles and shortening of the Co-R bond lengths; (c) lengthening of the Co-C bond; (d) deformation of the equatorial ligand unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope is the second-order rate constant, k II , which is related to K os and k 4 by eqn. (9); 2.59 (7) a…”
Section: Rate Constantsmentioning
confidence: 99%
“…2 O in trans-[Co(en) 2 Me(H 2 O)] 21 by pyrazole, 1,2,4-triazole and N-acetylimidazole indicate an I d mechanism 138. Bis(o-benzosemiquinonediiminato)(triphenylphosphane)cobalt(III), [Co III (s-BQDI) 2 (PPh 3 )(S)], where S is a molecule of solvent, undergoes substitution with imidazole and 4-dimethylaminopyridine in methanol or acetonitrile 139. The reactions feature an early step involving dissociation of a solvent molecule yielding a five-coordinate intermediate, followed by rate-determining combination with the nucleophile and loss of triphenylphosphane.…”
mentioning
confidence: 99%